Life Cycle Assessment of Diesel Fuel and Solar Pumps in Operation Stage for Rice Cultivation in Tanta, Nile Delta, Egypt. (2016) - Armanuos, Asaad M.; Negm, Abdelazim; Tahan, Abdel Hamid M.H. El
Abstract: This paper aims at using life cycle assessment (LCA) to assess the environmental impacts of groundwater pumping systems diesel fuel and solar power for lifting irrigation water for one feddan (1.037 acre) of rice. The study area lies in Tanta semi-arid central Nile Delta, Egypt. LCA via SimaProv8.04.30 is used to study the environmental impacts of pumping water using two types of pumping systems. Environmental impacts of diesel pump and solar pump systems are compared for different hydraulic head and area of rice cultivation scenarios. Results indicated that the diesel-powered pumping systems are more harmful to the environment than solar power pumps. The contribution to midpoint environmental impacts of the diesel fuel pump impacts reach 70% for natural resources, 18% for human health, 10% for climate change and 2% for ecosystem quality. On the other hand, solar pumping system contributes to 3% to climate change, 2% to human health and natural resources impacts, and 0.5% to ecosystem quality. The results confirm that for groundwater pumping, diesel fuel energy has the highest environmental impacts on human health, the ecosystem quality, climate change and resources depletion. It is highlighted that the type of power source must be considered when ranking pumping systems based on environmental performance.